2014
DOI: 10.1007/s00264-013-2261-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Levels (IL-4, IL-6, IL-8 and TGFβ) as Potential Biomarkers of Systemic Inflammatory Response in Trauma Patients

Abstract: Purpose Much research is now being conducted in order to understand the role of cytokines in the development of the inflammatory response following trauma. The purpose of this study was to evaluate whether serum levels of certain cytokines, measured immediately after initial injury, can be used as potential biomarkers for predicting the development and the degree of severity of the systemic inflammatory response (SIRS) in patients with moderate and severe trauma. Methods We conducted a prospective study with 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
75
3
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 32 publications
10
75
3
6
Order By: Relevance
“…Very high levels of IL-6 have been shown from the first hour after trauma [17], which is in agreement with the data from this study. Moreover, we found that IL-6 level were significantly higher in patients with MODS, which coincide with the results of other authors and allows to propose IL-6 as a marker for predicting both the development of SIRS, injury severity and clinical complications [17,18].…”
Section: Discussionsupporting
confidence: 89%
“…Very high levels of IL-6 have been shown from the first hour after trauma [17], which is in agreement with the data from this study. Moreover, we found that IL-6 level were significantly higher in patients with MODS, which coincide with the results of other authors and allows to propose IL-6 as a marker for predicting both the development of SIRS, injury severity and clinical complications [17,18].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, a systemic inflammatory response with increasing cytokine concentrations has been observed and correlated with the incidence of posttraumatic complications (e.g. pneumonia and MODS)48. In our model, both local and systemic inflammatory changes were found, supporting its clinical relevance49.…”
Section: Discussionsupporting
confidence: 74%
“…The anti-inflammatory cytokine level in rats showed that TGFβ levels were significantly higher in surgery groups than in group 1 in the later stage, and IL-10 levels were significantly higher in surgery groups than in group 1 throughout the entire process. The increase in pro-inflammatory cytokines is evident soon after injuries (6 h) and lasts usually for 24-48 h in most cases, and the duration of this reaction depends on the severity of the trauma and the basic state of the patient [27,28]. In our experiment, the inflammatory cytokines in rats' blood samples showed the similar trend as that in most clinical cases.…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, ELISA analysis of inflammatory cytokines was performed to evaluate the systemic inflammation after fractures. Skeletal and tissue injuries may cause a hyper-inflammatory reaction of the immune system manifested by elevation in levels of proinflammatory cytokines, and the massive secretion of proinflammatory cytokines usually induces upregulation of anti-inflammatory cytokines such as IL-4 and regulatory cytokines such as transforming growth factor-beta (TGFbeta) and IL-10, which results in a decrease of the severity of the inflammatory reaction [27,28]. In our study, compared with group 1 (control group), the levels of the proinflammatory cytokine TNF-α and IL-1β in groups 3 and 4 were significantly higher than those in groups 1 and 2.…”
Section: Discussionmentioning
confidence: 99%